2017
DOI: 10.18280/ijht.35sp0149
|View full text |Cite
|
Sign up to set email alerts
|

Energy savings evaluation for dry-cooler equipped plants in shopping mall buildings

Abstract: In the present paper the possible energy savings achievable by means of dry coolers adoption in cooling plants serving shopping mall buildings has been carried out. In these buildings, could happens that, due to internal gains caused by occupancy, lighting, and electrical devices, or because of solar radiation entering through the large skylights on the aisle, some zones have to be cooled also during the middle and the winter seasons. The aim of this work is the evaluation of the energy saving, reachable when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The findings suggest that also other designing procedures of building systems could be influenced by these differences (considering also the extreme temperatures variations). Among the others, the systems whose efficiency depends on weather conditions should be studied, for example heat pumps [35][36][37], evaporative cooling systems [13,14] or dry coolers [15][16][17] systems, that are relevant for large scale planning, energy savings, water and carbon footprint reduction [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that also other designing procedures of building systems could be influenced by these differences (considering also the extreme temperatures variations). Among the others, the systems whose efficiency depends on weather conditions should be studied, for example heat pumps [35][36][37], evaporative cooling systems [13,14] or dry coolers [15][16][17] systems, that are relevant for large scale planning, energy savings, water and carbon footprint reduction [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The Moisture Representative Year generation procedure presented in this work, is intended to produce representative years to be used in simulation tools that consider also the influence of rain, like the aforementioned ones. Moreover, the efficiency of some heating and cooling system components depends on the moisture content of air (for example the evaporative cooling systems [13,14], the dry cooler systems [15][16][17]) and thus, the results of the analysis would require a weather file selected also considering the weather variables related to moisture content of air. The heat and moisture transfer simulations of the walls are more frequently performed to evaluate the risks connected to the uncontrolled moisture migration.…”
mentioning
confidence: 99%
“…These efforts will create a favourable policy environment and standard market order for the promotion of green credit, and boost the on-going enhancement of technological innovation efficiency. In the meantime, commercial banks should improve their own management level and make use of the market forces to increase their operation efficiency [20][21][22]…”
Section: B Situation Evolution Simulationmentioning
confidence: 99%
“…Simulations of the first configuration are carried out by the authors in a previous work [9]. The investigated cooling system has been compared, in terms of energy consumption and overall coefficient of performance, with a configuration most widely used for commercial building, in which the water-cooled condensers of the chiller uses recirculation water from a cooling tower.…”
Section: Cooling Plant Systemsmentioning
confidence: 99%
“…In a previous study [9] authors evaluated the feasibility and the advantages to substitute cooling towers for dry-coolers. For different locations, TRNSYS simulations were carried out and the results shown that, in cities with a colder climate, there is a greater energy saving due to a lower value of the external mean air temperature; in particular, the city with the greatest annual energy saving amount (42.4%) is Hamburg, whereas the city with the lowest annual energy saving amount (14.2%) is Messina.…”
Section: Introductionmentioning
confidence: 99%